Healing the gospel: a radical vision for grace, justice, and the cross - Flood, Derek Henry (Wipf and Stock Publishers, 2012)
Intro -- Title Page -- Foreword -- Acknowledgments -- Chapter 1: The Limits of Law -- Chapter 2: God's Justice -- Chapter 3: Salvation Means Healing -- Chapter 4: Loving Sacrifice -- Chapter 5: Christus Victor -- Chapter 6: The Tyrant of Wrath -- Chapter 7: Incarnational Atonement -- Chapter 8: The Suffering Servant -- Chapter 9: The Theology of the Cross -- Chapter 10: A Crucified People -- Appendix -- Bibliography.